2009
DOI: 10.1016/j.jep.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity-guided fractionation from Araucaria angustifolia leaves extract

Abstract: The present study has shown that the hydroethanolic extract from Araucaria angustifolia leaves as well as many different fractions and subfractions exhibited antiherpes activity, supporting the use of this plant species in folk medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 34 publications
1
34
0
2
Order By: Relevance
“…Similarly, compounds 10 and 11 (pseudomolecular ions [M−H] − at m/z 865), could be assigned to Btype (epi)catechin trimers. In all instances, the fragmentation patterns were consistent with those expected for such types of compounds, i.e., similar to those observed for proanthocyanidins dimers but with Proanthocyanidins and biflavonoids have been previously described as the most abundant compounds in A. angustifolia (Freitas et al, 2009;Peralta et al, 2016;da Silva et al, 2014;Yamaguchi, Kato, & Di, 2009;Yamaguchi, Vassa, Kato, & Mascio, 2005). Nevertheless, to the best of our knowledge, a detailed characterization of the proanthocyanidin fraction in A. angustifolia seeds has not been previously described.…”
Section: Phenolic Compounds In Pinhão Extractssupporting
confidence: 83%
“…Similarly, compounds 10 and 11 (pseudomolecular ions [M−H] − at m/z 865), could be assigned to Btype (epi)catechin trimers. In all instances, the fragmentation patterns were consistent with those expected for such types of compounds, i.e., similar to those observed for proanthocyanidins dimers but with Proanthocyanidins and biflavonoids have been previously described as the most abundant compounds in A. angustifolia (Freitas et al, 2009;Peralta et al, 2016;da Silva et al, 2014;Yamaguchi, Kato, & Di, 2009;Yamaguchi, Vassa, Kato, & Mascio, 2005). Nevertheless, to the best of our knowledge, a detailed characterization of the proanthocyanidin fraction in A. angustifolia seeds has not been previously described.…”
Section: Phenolic Compounds In Pinhão Extractssupporting
confidence: 83%
“…A study conducted to confirm the popular use of leaves of A. angustifolia against Herpes Simplex Virus (HSV-1) showed that the ethyl acetate and n-butanol fractions obtained from the crude hydroalcoholic extract have the best antiherpetic activity (Freitas et al, 2009). Chemical analysis of this subfraction revealed the presence of proanthocyanidins and biflavonoids (bilobetin, II-7-O-methyl-robustoflavona and cupressuflavone), but the authors reported that the proanthocyanidins are possibly the main responsible for the anti-HSV-1 activity.…”
Section: Leaves Of a Angustifoliamentioning
confidence: 99%
“…Infusions of the bark are used topically to treat muscular tensions and varicose veins, while the syrup produced from the resin is used for the treatment of respiratory infections. Infusions of leaves are used as emollient, antiseptic, against respiratory infections, rheumatism, fatigue and anemia, and dyes are used for the treatment of wounds and herpes eruptions (Auler et al, 2002;Andrighetti-Frohner et al, 2005;Freitas et al, 2009). In view of the above, this review aims to summarize and evaluate the main findings related to the nutritional and therapeutic uses of A. angustifolia, with special attention to the chemical composition of the preparations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the powerful chemical characterization of the seeds, other parts of the tree are equally important. Studies have reported that the resin (found in the wood and knots), the dead bark (which is naturally discarded by the tree) and the leaves (needles) retain an intriguing chemical composition with dynamic biological activity [10][11][12][13][14][15][16]. Our group has importantly contributions regarding A. angustifolia biological effects.…”
Section: Introductionmentioning
confidence: 92%
“…Infusion of leaves (young or senescent) is orally used for the treatment of scrofula, fatigue and anemia, whereas tinctures from them are topically used on dermatological conditions such as dryness skin and wounds [21,22,24]. The leaves are also used to treat herpes disease, since they exhibit important antiviral activity [15]. Araucaria seeds are medically employed in treatment of heartburn, anemia and tumors [22,23].…”
Section: Figurementioning
confidence: 99%